Pengaruh Kualitas Laba Terhadap Kualitas Audit dengan Rasio Keuangan sebagai Variabel Kontrol - Darwin Marasi Purba (Universitas Andalas, 2019)
This research aims to examine the effect of the earnings quality and financial ratio's consists of return on asset and leverage on the audit quality. Measurement of audit quality in this research using formulas of addition and non-weighted approach from the audit quality index obiter of accountant's office size, auditor fees, audit opinion, audit tenure, and auditor specialization. This study is causal research with a quantitative approach. The population in this research is manufacturing sector companies listed on the Indonesian Stock Exchange in 2017. The sampling technique used purposive sampling and counting in an amount of 72 companies. Data collected using literature study and documentation. Data obtained through www.idx.co.idand company official website. Methods of data analysis using multiple regression analysis models. These results of this study indicate that earnings quality and the financial ratio have significant effects simultaneously test on the audit quality. However, partial test results showed that earnings quality, return on assets, and leverage have a significat effect on the audit quality.